THE DEVELOPMENT OF SCIENCES IN AL-QUR'AN PERSPECTIVES - Soleha, Soleha; Adrian, Adrian (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2015)
This research applied the method of interpretation and bi ’l-ra'y approach. It tried to reinvent the spirit of the Qur'an and Hadith to push humankind to develop science integratively and to make it beneficial for human beings and nature. The research confirmed that human beings as khalīfah fi ’l-arḍ, was given the right and freedom to explore what is on this earth and its contents with all its potential. Even in the Qur'an, Allah has made available all materials for the development of science, al ayah al-kawniyyah verses. Al-Qur'an as a resource of knowledge in Islam stated that one of the advantages human beings from the others is that they were endowed reason to search and explore science for the progress of human beings.***Penelitian ini dengan menggunakan metode interpretasi dan pendekatan bi ’l-ra'y, mencoba untuk menciptakan kembali semangat Qur'an dan Hadits untuk mendorong manusia untuk mengembangkan ilmu pengetahuan secara integratif dan membantu untuk manusia dan alam. Penelitian ini menegaskan bahwa manusia sebagai khalīfah fi ’l-arḍ, diberi hak dan kebebasan untuk dieksplorasi apa yang ada di bumi ini dan isinya dengan semua potensinya. Bahkan dalam al-Qur'an Allah telah menyediakan bahan-bahan untuk pengembangan ilmu pengetahuan, yang tentunya di sisi lain dengan ayat kawniyyah. Al-Qur'an sebagai sumber pengetahuan dalam Islam yang menyatakan bahwa salah satu keuntungan manusia dibandingkan makhluk yang lain adalah diberikan pikiran untuk mencari dan mengeksplorasi ilmu pengetahuan untuk kemajuan manusia.